Value Creation in Volatile Economies - Dias, Álvaro Lopes (2019)
This chapter presents in a simplified way that communities in volatile economies can create value through the identification, valorization, and operationalization of knowledge, traditions, and other cultural dimensions, many of them in the domain of tacit knowledge, available in the minds of people and community shared value. Through a cycle of identification of local knowledge, it is possible to begin the whole process, which necessarily passes through the cooperation between the various local actors. In a third phase, it is essential to structure the positioning, which represents the conceptual dimension concerning the way the community intends to present itself to the market. Next, it is essential to structure this offer, promoting value creation and capture. As such, the community should value their products or services by enhancing local knowledge and taking value creation initiatives in favor of local development (value capture).